Ischemic Hepatitis as the Presenting Manifestation of Cardiac Amyloidosis. (11th November 2014) - Petz, Chelsey A.; Todoran, Thomas; Rockey, Don C.
An abrupt elevation in aminotransferases without clear etiology may be attributed to hypoxic hepatitis. Underlying cardiac dysfunction, an important clinical clue, is often overlooked as a cause of hypoxic hepatitis, and understanding the interdependence of the heart and liver is crucial in making this diagnosis. Causes of cardiac dysfunction may include any of many different diagnoses; infiltrative heart disease is a rare cause of cardiac dysfunction, with amyloidosis being the most common among this category of pathologies. More advanced imaging techniques have improved the ability to diagnose infiltrative heart disease, thus allowing quicker diagnosis of conditions such as amyloidosis.